Gender Disparity from School Structure to Classroom Materials: A Critical Overview - Sanae ACHAG (International Journal of Scientific Research and Innovative Studies, 2024)
This article aims to scope gender disparity in various educational settings. It unveils gender gaps in schools, including gender in the workforce, the performance of teachers and students in classrooms, teachers’ practices, and gender representations in curriculum and hidden curriculum. Drawing from prior and recent literature reviews, the findings exhibit that gender stereotypes and disparities are still produced and shaped until the present time. Gender disparities in both academic and non-academic contexts remain noticeable at different levels. Typical gender roles are reinforced through the low ratio of women’s participation in school leadership positions. Teachers’ stereotypical practices, ideologies, methods, and classroom materials may negatively affect and alter students’ gender assumptions and thoughts, which increasingly deepens gender gaps. Therefore, the efforts and initiatives to diminish these gender gaps are still insufficient with the scarcity of serious radical changes in international educational policies and reforms. Keywords : gender disparities, gender gaps, gender stereotypes, schools. Received Date: June 25, 2024 Accepted Date: July 25, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/172 DOI: https://doi.org/10.5281/zenodo.13146975